Assessing biomimetic aquaporin membrane for forward osmosis desalination process: A dataset - Soleyman Sahebi; Nasim Fadaie; Leila Mirshekar; Bahram Kamarehie; Toraj Mohammadi (Data in Brief, 2019)
This paper presents the performance of aquaporin forward osmosis membrane using chemical fertilizers as a draw solution. The comprehensive evaluation conducted for five conventional fertilizers ((CO (NH2)2, KCl, CaCl2, (NH4)2SO4) and (NH4)2HPO4) as draw solutions. The diluted fertilizer can be used directly for farming as fertigation. In this process, DSs do not need to be recovered and it is a single step desalination process. The data include the characterization of the intrinsic properties of the membrane samples and their performance under FO and PRO modes of operations. In addition, the data for various draw solution concentration under feed solution with deferent total dissolved solids (TDS) were evaluated. For example, a water flux of 17.5 L m− 2 h− 1 and 23.92 g m−2 h−1 reverse solute flux (RSF) was achieved under the FO operation mode for 3 M KCl. Keywords: Forward osmosis, Aquaporin, Biomimetic membrane, Desalination, Fertigation